Genetic diversity and virulence of Bacillus cereus group isolates from bloodstream infections - Okutani, Akiko; Okugawa, Shu; Fujimoto, Fumie; Ikeda, Mahoko; Tsutsumi, Takeya; Moriya, Kyoji; Maeda, Ken (Microbiology spectrum, 2025)
This study provides novel insights into the genetic diversity and virulence potential of B. cereus strains causing bloodstream infections in a Japanese hospital setting. These findings suggest diverse infection pathways and highlight the importance of continuous molecular epidemiological surveillance for effective infection control.